2023
DOI: 10.1002/uog.26299
|View full text |Cite
|
Sign up to set email alerts
|

Urological complications in women undergoing Cesarean section for placenta accreta spectrum disorders: systematic review and meta‐analysis

Abstract: ObjectiveTo report the occurrence of urologic complications in women undergoing surgery for placenta accreta spectrum (PAS) disorders.MethodsMedline, Embase and Cochrane databases were searched electronically up to 1st of November 2022. Studies reporting cohort on surgical management and outcome of PAS. Two independent reviewers performed the data extraction using a predefined protocol and assessed the risk of bias using the Newcastle‐Ottawa scale for observational studies, with difference agreed by consensus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 99 publications
0
5
1
Order By: Relevance
“…The incidence of intraoperative urologic complication in the present study was lower than that reported in a recent systematic review and meta-analysis (9.4% vs 15.3%) 11 and involved only the upper part of the bladder. This can be explained by the high volume of cases and MDT expertise of nearly a decade in managing complex CDs 13 .…”
Section: Comparison With Other Studiescontrasting
confidence: 84%
See 2 more Smart Citations
“…The incidence of intraoperative urologic complication in the present study was lower than that reported in a recent systematic review and meta-analysis (9.4% vs 15.3%) 11 and involved only the upper part of the bladder. This can be explained by the high volume of cases and MDT expertise of nearly a decade in managing complex CDs 13 .…”
Section: Comparison With Other Studiescontrasting
confidence: 84%
“…The use of three controls for each individual case, matched for the main risk factors of PAS in subsequent pregnancy, should limit the risk of bias in the present analysis of the data. Another limitation is the exclusion of cases requiring emergency delivery prior to planned surgery, which are known to be associated with a higher risk of intraoperative urologic complications 11 . The single-institution study design may also limit the generalizability of our results.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will disproportionately impact rural and low-income patients, highlighting health disparities and barriers to accessing adequate healthcare for some patient populations. Considering that patients with placenta percreta and those undergoing emergency surgical intervention have a high risk of urological complications further displays the need of early diagnosis to allow the transfer of patients to medical centers equipped for such complications [ 35 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…Pelvic radiotherapy for malignancy decreases the blood supply, leading to tissue necrosis, sloughing, and fistula formation, even after many years [34]. Intriguingly, due to the fact that the incidence of placenta accreta spectrum is increasing as a result of the rising Cesarean section rate, some research suggests that this may be a future risk factor for an increase in VVFs [35].…”
Section: Etiologymentioning
confidence: 99%